To determine the correct demonstration of polynomial subtraction, let's perform the subtraction step by step:
We need to calculate:
\[ (2x^2 + 6x + 1) - (3x^2 + 3x + 9) \]
First, distribute the negative sign to the second polynomial:
\[ 2x^2 + 6x + 1 - 3x^2 - 3x - 9 \]
Now, combine like terms:
-
Combine the \( x^2 \) terms: \[ 2x^2 - 3x^2 = -1x^2 \text{ or } -x^2 \]
-
Combine the \( x \) terms: \[ 6x - 3x = 3x \]
-
Combine the constant terms: \[ 1 - 9 = -8 \]
Putting it all together, we get:
\[ -x^2 + 3x - 8 \]
Now we can check the given options:
- \((2x^2+6x+1)-(3x^2+3x+9)=5x^2+9x+10\) — Incorrect.
- \((2x^2+6x+1)-(3x^2+3x+9)=x^2+3x+8\) — Incorrect.
- \((2x^2+6x+1)-(3x^2+3x+9)=-x^2+3x-8\) — Correct.
- \((2x^2+6x+1)-(3x^2+3x+9)=-5x^2+3x-8\) — Incorrect.
The correct answer is:
\((2x^2+6x+1)-(3x^2+3x+9)=-x^2+3x-8\)